John H. answered • 12/20/18

MBA Graduate, Available for Accounting and Other Business Tutoring

So, here is how I get there, it is important to understand the order of operations when solving my equation:

**7**^{2}** - (12 x 3) + 2**^{4}** = 29**

By order of operations we know that parenthesis are solved first and 12 x 3 = 36:

7^{2} - 36 + 2^{4}

Now we would solve the exponential components so 7 x 7 = 49 and 2 x 2 x 2 x 2 = 16:

49 - 36 + 16 = 29

Remember in order of operations, multiplication and division occur at the same time. The same is true for addition and subtraction. I personally just solve from left to right.

49 - 36 = 13

13 + 16 = **29**

This is the way I got there, but possibly someone else solved it differently.

Hope this helped!

JD